Pengendalian Kualitas Kemasan Fleksibel dalam Meminimalisasi Produk Cacat pada Proses Laminasi Ekstrusi - Dewanto, Yahya; Galingging, Rumbel; Asissi Ismoyo Winandi, Fransiskus (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2022)
This research is based on the total loss of X company in April 2022 which exceeds the specified standard. The extrusion lamination process is a part that produces many defective products. Therefore, this study is aimed at finding the dominant problem that occurs in the extrusion lamination process and reducing defective products in the extrusion lamination process according to the cause. This study was structured using quantitative methods with a causal research design that states a cause-and-effect relationship. The analysis technique in this study uses Pareto diagrams, FMEA and causal diagram as problem solving tools. The results of the study show that the cause of uneven lamination in the extrusion lamination process at PT X is caused by the lack of human resource capabilities, poor quality control systems, and poorly maintained machines. This research produces suggestions for improvements that can be used by the company to make preventive steps in the next extrusion lamination process.